Development of DragGAN application for photographers - Takesawa, Saori (Nanyang Technological University, 2024)
Amidst the evolving landscape of AI art, DragGAN emerges as a powerful AI image editing tool with intuitive image feature manipulation. Through DragGAN, users can effortlessly adjust specific features of an image by simply clicking and dragging, revolutionizing the post-processing workflow for photographers seeking to elevate their creative output. This intuitive functionality not only streamlines the editing process but also eliminates the need for extensive image manipulation skills, catering to photographers of all proficiency levels. However, the technical intricacies and terminology of DragGAN limits its accessibility to users familiar with the AI field, posing barriers of its adoption among the photography community. In response to these challenges, the development of Simple DragGAN—an application aimed at simplifying DragGAN's functionalities—has been undertaken. By presenting a user-friendly interface and streamlined features, Simple DragGAN aims to democratize access to DragGAN's capabilities, thereby fostering broader engagement with AI-driven artistry. Moreover, the exploration of training custom image-generating models to enable personalized image editing experiences represents a promising avenue for future development. While not currently feasible for integration into the application, this endeavour underscores the ongoing pursuit of enhancing user-centric solutions within the realm of AI art.